Compound danshen dripping pills vs. nitrates for stable angina pectoris: a systematic review and meta-analysis - Zhang, Mengying; Wang, Wenjia; Sun, He; Zhai, Jingbo; Hu, Yunhui (Frontiers in Cardiovascular Medicine, 2023)
Background: Long-term use of nitrates for treating stable angina pectoris (SAP) may lead to patients' tolerance to nitrates. As a traditional Chinese medicine, Compound danshen dropping pills (CDDP) is beneficial for patients with SAP. This study aimed to critically assess the efficacy and safety of CDDP versus nitrates for SAP. Methods: PubMed, Embase, Web of Science, Cochrane library, CNKI, Wanfang Digital Periodicals, and Chinese Science and Technology Periodicals database were searched from inception to April 2023. Randomized controlled trials (RCTs) comparing CDDP with nitrates for SAP were included. The meta-analysis was conducted to estimate the pooled effect. Results: Twenty-nine studies were included for the statistical analysis. The meta-analyses with the random-effect model indicated that CDDP could significantly increase the effective rate in symptom improvement compared with nitrates (Pooled 9 RCTs, OR = 1.95, 95% CI: 1.25 to 3.05, P = 0.003, duration of 4 weeks; Pooled 4 RCTs, OR = 3.45, 95% CI: 1.84 to 6.48, P = 0.0001, duration of 6 weeks; Pooled 13 RCTs, OR = 4.02, 95% CI: 2.14 to 7.57, P＜0.0001, duration of 8 weeks). The meta-analyses with the random-effect model indicated that CDDP could significantly increase the effective rate in electrocardiogram improvement compared with nitrates (Pooled 5 RCTs, OR = 1.60, 95% CI: 1.02 to 2.52, P = 0.04, duration of 4 weeks; Pooled 3 RCTs, OR = 2.47, 95% CI: 1.60 to 3.82, P < 0.0001, duration of 6 weeks; Pooled 11 RCTs, OR = 3.43, 95% CI: 2.68 to 4.38, P＜0.00001, duration of 8 weeks). The incidence of adverse drug reactions in the CDDP group was lower than that in the nitrates group (Pooled 23 RCTs, OR = 0.15, 95% CI: 0.1 to 0.21, P < 0.00001). The results of the meta-analyses with fixed-effect model were similar with above results. The levels of the evidence ranged from very low to low. Conclusion: The present study suggests that CDDP with the duration of at least 4 weeks can be considered as an alternative to nitrates for treating SAP. However, more high-quality RCTs are still needed to confirm these findings.